2016
DOI: 10.1109/tlt.2015.2470683
|View full text |Cite
|
Sign up to set email alerts
|

VirTUal remoTe labORatories Management System (TUTORES): Using Cloud Computing to Acquire University Practical Skills

Abstract: The use of practical laboratories is a key in engineering education in order to provide our students with the resources needed to acquire practical skills. This is specially true in the case of distance education, where no physical interactions between lecturers and students take place, so virtual or remote laboratories must be used. UNED has developed a system to create and manage virtual remote laboratories, aimed at improving the way how practical exercises are conducted. This system is based on cloud compu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(22 citation statements)
references
References 27 publications
0
22
0
Order By: Relevance
“…For example, in class Clicker use allowed engagement with and understanding of the coursework (Flosason et al , ) and before class polling was suggested to allow for a better prepared student (Sun, Martinez, & Seli, ). There was findings from two studies that student activity visibility and monitoring in a VLE improved the academics potential to diagnose and deal with students’ problems more efficiently, though with academic staff time implications (Caminero et al , ; Lafuente Martínez et al , ).…”
Section: Academic Staff Efficienciesmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, in class Clicker use allowed engagement with and understanding of the coursework (Flosason et al , ) and before class polling was suggested to allow for a better prepared student (Sun, Martinez, & Seli, ). There was findings from two studies that student activity visibility and monitoring in a VLE improved the academics potential to diagnose and deal with students’ problems more efficiently, though with academic staff time implications (Caminero et al , ; Lafuente Martínez et al , ).…”
Section: Academic Staff Efficienciesmentioning
confidence: 99%
“…Transparency and visibility-student work There was an aspirational sense that efficiencies may be generated through enhanced ability of academic staff to monitor student activity (Caminero et al, 2016;Flosason et al, 2015;Lafuente Martínez et al, 2015;Zou, 2013). For example, in class Clicker use allowed engagement with and understanding of the coursework (Flosason et al, 2015) and before class polling was suggested to allow for a better prepared student (Sun, Martinez, & Seli, 2014).…”
Section: Workload Efficiencies-time-savingsmentioning
confidence: 99%
“…Such a technological choice allows for a centralized virtualization and re-use of low-performing legacy computers, as well as deploying applications without the need to buy many licenses. Moreover, some cloud-based learning environments have been devised ad hoc for virtual laboratories in different fields [18,20], thus allowing institutions, after specific agreements, to exploit laboratories of other universities or research centers. Nevertheless, the cloud could raise some issues, such as the inability to implement a pay-per-use scheme and open-source solutions or what is called vendor lock-in.…”
Section: Institutionsmentioning
confidence: 99%
“…The proposed solution sheds light on the importance of carefully adapting, on the part of a dedicated IT staff, the different layers of the cloud to the specific laboratory, with particular care to micro-controllers, local servers, pieces of middleware, appropriate operating systems and devices (Arduino, Raspberry Pie, etc.). In [20], another system for virtual laboratories is presented. This solution takes advantage of remote access to virtual machines (Virtual Remote Labs) and needs IT staff to isolate virtual machines during certain time frames, when they have to be connected to actual physical devices or with network equipment.…”
Section: It Staffmentioning
confidence: 99%
“…For example, in the course selection node system, the system server is often unable to withstand high traffic, leading to the phenomenon of course selection congestion, which affects the orderly teaching work [5].…”
Section: Data Storage and Management Pressurementioning
confidence: 99%